Association of internet use and depression among the spinal cord injury population - Tsai, I-Hsuan; Graves, Daniel E; Lai, Ching-Huang; Hwang, Lu-Yu; Pompeii, Lisa A (Archives of physical medicine and rehabilitation, 2014)
To examine the relation between the frequency of Internet use and depression among people with spinal cord injury (SCI). Cross-sectional survey. SCI Model Systems. People with SCI (N=4618) who were interviewed between 2004 and 2010. Not applicable. The frequency of Internet use and the severity of depressive symptoms were measured simultaneously by interview. Internet use was reported as daily, weekly, monthly, or none. The depressive symptoms were measured by the Patient Health Questionnaire-9 (PHQ-9), with 2 published criteria being used to screen for depressive disorder. The diagnostic method places more weight on nonsomatic items (ie, items 1, 2, and 9), and the cut-off method that determines depression by a (PHQ-9) score ≥10 places more weight on somatic factors. The average scores of somatic and nonsomatic items represented the severity of somatic and nonsomatic symptoms, respectively. Our multivariate logistic regression model indicated that daily Internet users were less likely to have depressive symptoms (odds ratio=.77; 95% confidence interval, .64-.93), if the diagnostic method was used. The linear multivariate regression analysis indicated that daily and weekly Internet usage were associated with fewer nonsomatic symptoms; no significant association was observed between daily or weekly Internet usage and somatic symptoms. People with SCI who used the Internet daily were less likely to have depressive symptoms.